Tenosynovial giant cell tumor of the suboccipital region – A rare, benign neoplasm in this location. (August 2020) - Singh, Rahul; Stienen, Martin N.; Ganjoo, Kristen; Kolahi, Kevin S.; Cayrol, Romain; Charville, Gregory W.; Born, Donald E.; Zygourakis, Corinna C.
Highlights: Tenosynovial giant cell tumors (TGCT) are benign lesions that arise from the synovium of tendon sheaths, bursae, and joints. Spinal involvement is rare and usually associated with the synovial membrane of the facet joints. Surgical gross total resection is curative and should be the aim of treatment. Imatinib has been has shown promising results in tumors that are unresectable. Abstract: Tenosynovial giant cell tumors (TGCTs) are benign neoplasms that arise from the synovium of tendon sheaths, bursae, and joints. We report a rare presentation of TGCT involving the suboccipital spine.